1998
DOI: 10.1021/jo9705576
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Modified Uridine Bisvinyl Sulfone:  Synthesis of a Bifunctionalized Nucleoside Michael Acceptor and Its Use in Stereoselective Tandem Cyclization

Abstract: A bisvinyl sulfone functionality is incorporated into the carbohydrate moiety of uridine to synthesize 6 (or 7) which is a bifunctionalized nucleoside Michael acceptor and has the potential to form covalent bond with biological nucleophiles. This compound could be used to generate a large number and a new class of bicyclic S,S-dioxidethiazine derivatives 8-12 in stereoselective fashion. Compound 6 is also useful for the synthesis of a wide variety of monosubstituted compounds 13-15. The structures of compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…1 was that “the best results were obtained with protic solvents such as methanol ...” (Scheme 3, page 55) 1. In our paper,2 we reported on the use of MeOH for the cyclisation reaction and observed (page 1755; ref. 15)2 that the “selection of solvent was important” for this reaction and cyclisation did not occur in CHCl 3 .…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…1 was that “the best results were obtained with protic solvents such as methanol ...” (Scheme 3, page 55) 1. In our paper,2 we reported on the use of MeOH for the cyclisation reaction and observed (page 1755; ref. 15)2 that the “selection of solvent was important” for this reaction and cyclisation did not occur in CHCl 3 .…”
mentioning
confidence: 79%
“…Several years back we published a paper on the synthesis and reactions of nucleoside‐based divinyl sulfone. Although we did not synthesise any macrocycle in this paper, we did synthesise several bicyclic derivatives by treating various primary amines with the nucleoside‐based divinyl sulfone as shown below 2 …”
mentioning
confidence: 99%
“…Thiol is converted to a nucleophilic thiolate anion, which reacts with an epoxide to give a ring-opened sulfide, in the presence of TMG (1) [74]. A carbapenem antibiotic carrying a sulfide function was synthesized practically by the addition-elimination reactions of a thiol to the enol phosphate of b-keto ester in the presence of TMG (1) as a key step [75] (Scheme 4.27).…”
Section: Sulfide Formationmentioning
confidence: 99%
“…This latter method (Michael addition) has been developed by Chattopadhyaya et al as a powerful means for the synthesis of a large variety of modified nucleosides, including bicyclic nucleosides [14]. Recently, Pathak et al [15] reported the synthesis of 1,4-thiazinane (thiomorpholine)-fused uridine derivatives in 2',3'-position via Michael addition of amines to bisvinylsulfonyl uridine. Intramolecular Michael addition has been employed to construct cyclic structures of natural and synthetic compounds, but no such application has been elaborated in the field of nucleoside chemistry [16].…”
mentioning
confidence: 99%